2020
DOI: 10.1016/j.kint.2020.04.040
|View full text |Cite
|
Sign up to set email alerts
|

Different subpopulations of kidney interstitial cells produce erythropoietin and factors supporting tissue oxygenation in response to hypoxia in vivo

Abstract: Genetic induction of hypoxia signaling by deletion of the von Hippel-Lindau (Vhl) protein in mesenchymal PDGFRb D cells leads to abundant HIF-2 dependent erythropoietin (EPO) expression in the cortex and outer medulla of the kidney. This rather unique feature of kidney PDGFR-b D cells promote questions about their special characteristics and general functional response to hypoxia. To address these issues, we characterized kidney PDGFR-b D EPO expressing cells based on additional cell markers and their gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 53 publications
2
36
0
Order By: Relevance
“…4,10,29,[33][34][35] Resident fibroblasts and pericytes express the platelet derived growth factor receptor β (PDGFR-β) and are one of the most numerous cell types in the kidney. 4,9,31,36 A recent study also confirmed PDGFR-β + cells as the main precursors for myofibroblasts in human kidneys. 35 These PDGFR-β + cells also include all kidney cells able to produce EPO.…”
Section: Introductionmentioning
confidence: 70%
See 3 more Smart Citations
“…4,10,29,[33][34][35] Resident fibroblasts and pericytes express the platelet derived growth factor receptor β (PDGFR-β) and are one of the most numerous cell types in the kidney. 4,9,31,36 A recent study also confirmed PDGFR-β + cells as the main precursors for myofibroblasts in human kidneys. 35 These PDGFR-β + cells also include all kidney cells able to produce EPO.…”
Section: Introductionmentioning
confidence: 70%
“…Localization of mRNA expression was studied with the RNAscope® Multiplex Fluorescent v2 kit (Advanced Cell Diagnostics ACD, Hayward, CA, USA), according to the manufacturer´s instructions. 9,43 Kidneys were perfusion-fixed with 10% neutral buffered formalin solution, dehydrated in an ethanol series and embedded in paraffin. Hybridization signals were detected on 5µm tissue sections using the TSA® Plus fluorophores Cy3 and Cy5 (PerkinElmer, Waltham, Massachusetts…”
Section: In Situ Hybridization Via Rnascope®mentioning
confidence: 99%
See 2 more Smart Citations
“…Although CD73 has ubiquitous expression (12), recent single cell profiling experiments show that its mRNA is zonally distributed in epithelial tissues, including the liver (16), intestine (17), and kidney (18). CD73 is transcriptionally induced by hypoxia (19) and CD73-generated adenosine directly protects multiple epithelial tissues, including the liver, against hypoxic injury (20)(21)(22).…”
mentioning
confidence: 99%